Code-based new approaches for determining the minimum required separation gap. (December 2022) - Kamal, Muhammet
Abstract: This study aims to propose new approaches based on building height that do not require lateral displacement calculations to predict the separation gap distances between adjacent RC buildings. A total of 3696 nonlinear dynamic analyses were carried out using 66 different ground motion records for 56 adjacent buildings. The minimum required seismic gap distances calculated from the analysis results were compared with the building height-related requirements of some building codes or provisions (Turkish Building Earthquake Code, ASCE/41-17 and Australian code). The analysis results show that the ASCE/41-17 and Australian code provide overestimate gap distance, while the TBEC requirements are inconsistent according to the period ratio of adjacent buildings. The improved approaches with the proposed new equations for TBEC and ASCE/41-17 can be used effectively to prevent structural pounding of adjacent RC buildings located on different soil types. Besides, the proposed approach for different soil types provides better estimates between 66% and 94% of the 56 adjacent building models compared to the Double Difference Combination method known as DDC. The improved approaches in this study based on building height that do not require lateral displacement calculations to predict the safe separation distances between adjacent buildings are simple and useful for the evaluation of existing low and mid-rise RC frame buildings with no structural irregularity.